Muscle size-scaled shear elastic modulus: A muscle force index independent of maximal voluntary contraction, assessed during elbow extension. (9th November 2020) - Yagi, Masahide; Tateuchi, Hiroshige; Umehara, Jun; Motomura, Yoshiki; Hirono, Tetsuya; Nojiri, Shusuke; Pataky, Todd C.; Ichihashi, Noriaki
Abstract: Shear elastic modulus (G) can differ among individuals due to muscle size and other factors, even for constant muscle force. Inter-individual comparisons of G usually require normalization by maximal voluntary contraction (MVC), but MVC procedures may not be appropriate for certain clinical populations including those presenting with pain or other compromised functionality. This study aimed to test whether muscle size-scaled G, which does not require MVC testing, would yield stronger correlation with absolute torque than unscaled G. Twelve-healthy males performed isometric elbow extension across a range of torque magnitudes (from 5 Nm until 60% MVC). G of the triceps brachii was measured using shear wave elastography during each trial. Cross-sectional area (CSA) and muscle thickness (MT) of the triceps brachii were measured at rest. Scaled G was calculated as a product of G and CSA or MT ("G-CSA" and "G-MT", respectively). Within-individual linear regressions were conducted between absolute torque and the three force indicator variables. The regression slopes' coefficient of variation (CV) was calculated for each indicator across individuals. Between-individual correlation coefficients were calculated, after pooling all data across individuals into a single regression analysis for each indicator. Linear regression found that inter-individual slope variation increased in the following order: G-CSA, G-MT, and unscaled G (CV = 0.15, 0.18, and 0.29, respectively). Pooled-individual correlation coefficients were significantly higher in G-CSA and G-MT than in unscaled G (r = 0.948, 0.924, and r = 0.783, respectively). These results suggest that muscle size-scaled G may be more appropriate than unscaled G when comparing shear moduli across individuals.